Analysis by Vibrational Spectroscopy of Seaweed Polysaccharides with Potential Use in Food, Pharmaceutical, and Cosmetic Industries. (12th March 2013) - Pereira, Leonel; Gheda, Saly F.; Ribeiro-Claro, Paulo J. A.
Abstract : Polysaccharides present in several seaweeds ( Kappaphycus alvarezii, Calliblepharis jubata, and Chondrus crispus —Gigartinales, Rhodophyta; Gelidium corneum and Pterocladiella capillacea —Gelidiales, Rhodophyta; Laurencia obtusa —Ceramiales, Rhodophyta; Himanthalia elongata, Undaria pinnatifida, Saccorhiza polyschides, Sargassum vulgare, and Padina pavonica —Phaeophyceae, Ochrophyta) are analyzed by spectroscopic techniques. The nature of the polysaccharides (with extraction and without any type of extraction) present in these seaweeds was determined with FTIR-ATR and FT-Raman analysis of extracted phycocolloids and ground dry seaweed.